Reflections on Elwyn Richardson Commemoration. Issue 7 (6th June 2016) - Devine, Nesta
Abstract: This article was written as the final presentation to be delivered at our day of reflection on the educational work of Elwyn Richardson. As such, the tone is somewhat different to that which is usual for this journal, but I elect to leave it substantially the same as it was when delivered. I address first the question of what we do when we mourn or remember someone like Elwyn Richardson, who made an important contribution to New Zealand's educational history. Then I turn to a 'whakapapa' or genealogy of progressivist ideas in education in New Zealand, and finally look to where we might take the spirit of these ways of thinking in the future.